Lysosomal dysfunction promotes cleavage and neurotoxicity of tau in vivo - Khurana, V; Elson-Schwab, I; Fulga, T; Sharp, K; Loewen, C; Mulkearns, E; Tyynelä, J; Scherzer, C; Feany, M (2010)
Expansion of the lysosomal system, including cathepsin D upregulation, is an early and prominent finding in Alzheimer's disease brain. Cell culture studies, however, have provided differing perspectives on the lysosomal connection to Alzheimer's disease, including both protective and detrimental influences. We sought to clarify and molecularly define the connection in vivo in a genetically tractable model organism. Cathepsin D is upregulated with age in a Drosophila model of Alzheimer's disease and related tauopathies. Genetic analysis reveals that cathepsin D plays a neuroprotective role because genetic ablation of cathepsin D markedly potentiates tau-induced neurotoxicity. Further, generation of a C-terminally truncated form of tau found in Alzheimer's disease patients is significantly increased in the absence of cathepsin D. We show that truncated tau has markedly increased neurotoxicity, while solubility of truncated tau is decreased. Importantly, the toxicity of truncated tau is not affected by removal of cathepsin D, providing genetic evidence that modulation of neurotoxicity by cathepsin D is mediated through C-terminal cleavage of tau. We demonstrate that removing cathepsin D in adult postmitotic neurons leads to aberrant lysosomal expansion and caspase activation in vivo, suggesting a mechanism for C-terminal truncation of tau. We also demonstrate that both cathepsin D knockout mice and cathepsin D-deficient sheep show abnormal C-terminal truncation of tau and accompanying caspase activation. Thus, caspase cleavage of tau may be a molecular mechanism through which lysosomal dysfunction and neurodegeneration are causally linked in Alzheimer's disease. © 2010 Khurana et al.